Philosophy of humor in the poetry of Mohamed El Hihyawi between strategies and mechanisms - bahgt, nabil (El Omda in Linguistics and Discourse Analysis, 2024)
This study attempts, through the analytical approach and some theories of laughter and humor, to identify the strategies and mechanisms of humor in the poetry of Muhammad al-Hihyawi, to understand its significance, philosophy, and construction methods. The study relied on his poems, which he published in Al-Kashkul magazine in the period between 1924-1939, where Al-Hihyawi relied on several basic strategies for formulating humor in those poems, such as disguise, coding, poem structure (form), caricature, and verbal humor. These strategies were achieved through a number of different mechanisms through which Muhammad al-Hiyhawi formulated his humorous philosophy in his poetry, which he founded on a critical approach that uses confrontation and exposure to highlight the need for reform and change for the better.